Whole-Genome Resequencing Reveals Phylogenetic Relationships and Sex Differentiation Mechanisms Among Fujian Cycas Species - Xinyu Xu; Yousry A. El-Kassaby; Sijia Liu; Juan Zhang; Lanqi Zhang; Junnan Li; Wenkai Li; Kechang Zhang; Minghai Zou; Zhiru Lai; Likuang Lin; Yongdong Zhang; et al. (Horticulturae)
Cycads, renowned as “living fossils”, are among the most ancient extant seed plants, playing a crucial role in understanding plant evolution and sex differentiation. Despite their importance, research on their genetics and sex differentiation remains scarce. This study investigates three species, represented by six samples, collected from various regions in Fujian Province, China, using whole-genome resequencing on the Illumina platform. The sequence data underwent rigorous quality control, alignment, and variant detection, focusing on SNP and InDel distribution and annotation. Among the studied species, Cycas revoluta exhibited the highest number of SNPs and the greatest heterozygosity values. Based on SNP data, phylogenetic trees and principal component analysis revealed distinct clusters, with the three C. revoluta samples forming one cluster, while the two C. szechuanensis samples and the C. taiwaniana sample were grouped separately. Gene function using COG and GO annotations, and KEGG enrichment analysis, all highlighted differences in genomic structure and functional gene distribution between male and female cycads. Notably, genes associated with sex differentiation, such as MADS-box and auxin-responsive protein genes, were shown, while other transcription factors showed distinct annotations and enrichment patterns based on sex. This study improves our understanding of genetic variation, evolutionary relationships, and gene enrichment in cycads, providing a foundation for conservation, cultivation, and insights into sex differentiation mechanisms in these ancient plants.